2020
DOI: 10.3390/ijerph17197110
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Economic Status and Satisfaction with Homestead Withdrawal Policy: Expectation and Perceived Value

Abstract: The withdrawal of homesteads is an effective way to improve the efficiency of rural construction land use and is being piloted in many regions of China, but the mechanism influencing farmers’ satisfaction with the withdrawal policy is unclear. This paper aimed to investigate the relationships among farmers’ economic status (ES), policy expectation (PE), policy perceived value (PPV), and farmers’ satisfaction with homestead withdrawal policy (policy satisfaction; PS). The study examined the mediating effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
3
14
0
3
Order By: Relevance
“…Through a review of previous studies, we found that few works have analyzed issues relative to rural entrepreneurial construction land, and these studies have mainly focused on the status, policies, and other aspects. Some scholars have noticed that there are large amounts of wasteland and residential land in rural areas that have been extensively left idle for a long time [27][28][29][30][31][32]; however, there are no clear answers to how to use these marginal land resources to support rural entrepreneurship and development. In our study, we believe that the utilisation of idle land in rural areas, such as idle farmhouses, workshops, and school buildings, can be improved by innovative use and transformed into land for production, which is an effective way to alleviate the problem of land use for rural entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…Through a review of previous studies, we found that few works have analyzed issues relative to rural entrepreneurial construction land, and these studies have mainly focused on the status, policies, and other aspects. Some scholars have noticed that there are large amounts of wasteland and residential land in rural areas that have been extensively left idle for a long time [27][28][29][30][31][32]; however, there are no clear answers to how to use these marginal land resources to support rural entrepreneurship and development. In our study, we believe that the utilisation of idle land in rural areas, such as idle farmhouses, workshops, and school buildings, can be improved by innovative use and transformed into land for production, which is an effective way to alleviate the problem of land use for rural entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…农村宅基地按集体经济组织成员资格权进行 分配, 无偿获得、 无限期使用 [1] , 是中国农村重要的 福利性土地制度安排, 为保障农民 "居有定所" 及农 村社会稳定发挥了重要作用 [2] [5,6] [21] ; 家庭抚 养子女数量、 宅基地退出风险预期、 区位条件、 宅基 地面积及使用收益、 农户产权认知等阻碍农户宅基 地退出意愿 [12,22] 。此外, 经济发展水平及农户所处 家庭生命周期阶段也影响农户宅基地退出意愿, 经 济发展水平越高, 农户退地时考虑的因素也越多, 尤其是其家庭的资产和财产性收入状况 [23] 。有学者 将农户家庭按生命周期划分为夫妇核心家庭、 成长 核心家庭, 成熟核心家庭、 扩大家庭Ⅰ、 扩大家庭Ⅱ Tian 等 [10] 、 Wu 等 [11] 、 Zhao 等 [12] 、 Zhang [13] 、 Lu 等 [14] 、 Gu 等 [15] 、 Kong 等 [16] 、 Lyu 等 [17] 、 Zhang 等 [18] 、 Tang 等 [19] 、 Song 等 [20] 第 43 卷 第 7 期 资 源 科 学 http://www.resci.net 和萎缩家庭 6 个阶段, 其退出意愿呈现先增加后降 低再增加的 "N" 形变化趋势, 成熟核心家庭和萎缩 家庭的退地意愿是 2 个高值段 [24] 。…”
Section: 引言unclassified
“…(1) 激励与约束机制。构建积极的激励机制可 有效激发农户宅基地退出意愿, 促进其宅基地退出 行为 [12] 补偿方式, 以及完善社会保障体系、 制定就业优惠 政策等 [28] 。反向约束机制则通过较为严格的措施引 导农户将闲置及违建宅基地退出 [12] , 例如增加农户 闲置宅基地的持有成本, 或以宅基地面积为标准采 用递增收费法倒逼农户退出宅基地 [29] 。…”
Section: 宅基地退出机制unclassified
See 1 more Smart Citation
“…Some studies have reviewed the process through related institutional changes (Wu et al , 2018). Some others have assessed the appropriate compensation for peasants in WRH (Zhao et al , 2020). Yet others have assessed factors influencing peasants' willingness to withdraw from their homestead (Chen et al , 2017).…”
Section: Introductionmentioning
confidence: 99%